PENGELOLAAN SAMPAH DI KELURAHAN DADOK TUNGGUL HITAM KECAMATAN KOTO TANGAH KOTA PADANG - Wahyuni, Desi; Erita, Yeni; PrariKeslan, Widya (Pendidikan Geografi, 2013)
Desi Wahyuni, (2013). Waste Management in the  Dadok Tunggul Hitam  Koto Tangah  Padang This study aims to determine the Solid Waste Management in the  Dadok Tunggul Hitam Koto Tangah Padang.This research is descriptive. Population in this research is the a family that is in the Dadok Tunggul Hitam Koto Tangah. Totaling 3262 KK. Samples were taken in two ways, the samples were taken by purposive sampling areas (designation) by taking 3 RW in the Dadok Tunggul Hitam. 1(RW III 492), 2(RW IV 368), 3(RW V 306). The reason this area is the determination of the sample due to the three areas mentioned above is a region that has the highest population in the Dadok Tunggul Hitam, while the proportion of respondents in a sample taken at 10% of total, so the population of 117 families. Techniques of data collection through questionnaires or instrument. Teknik analyzed using percentage formula.The research found that: (1) Awereness of the waste management in the Dadok Tunggul Hitam Koto Tangah Padang on both criteria, with a percentage of 85,52% (2) Public participation on waste management in the Dadok Tunggul Hitam Koto Tangah is at criteria quite well, with a percentage of 73,74%, and (3) the motivation for waste management in urban dadok koto hands of stubble on criteria including good, with a percentage of 68,66%.From the above discussion, it can be concluded that : (1) Public awareness of the average score is 3,421 with 85,52% of respondents rate the performance on both criteria. This shows that waste management including good and this needs to be maintained and preserved. (2) Community participation is the average score of 3,09 with 77,24% respondents level of achievement on the criteria that are pretty good. This shows that community participation in waste management including good enough and it needs to be fixed, and (3) the motivation average score is 2,761 with 69,03% of respondents level of achievement on the criteria that are pretty good. This suggests that the motivation of the community in waste management including good enough and it needs to be improved.